2017
DOI: 10.1007/s40520-016-0720-5
|View full text |Cite
|
Sign up to set email alerts
|

Chronic obstructive pulmonary disease and long-term mortality in elderly subjects with chronic heart failure

Abstract: Multivariate analysis indicates that CHF (Hazard risk = 1.67, 95% confidence interval 1.15-3.27, p < 0.031) and COPD (Hazard risk = 1.27, 95% confidence interval = 1.08-1.85, p < 0.042) were predictive of longterm mortality. When CHF and COPD simultaneously occurred, the risk dramatically increased up to 3.73 (95% confidence interval = 1.19-6.93, p < 0.001). Conclusions Long-term follow-up showed higher mortality among elderly subjects affected by CHF or COPD. Simultaneous presence of CHF and COPD significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
11
0
2
Order By: Relevance
“…Testa et al found that patients with COPD and CHF had an increased risk of mortality compared with patients with either COPD or CHF alone. [27] The results of the present study were consistent with their study. There are some potential pathophysiological mechanisms that could explain the interaction between COPD and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…Testa et al found that patients with COPD and CHF had an increased risk of mortality compared with patients with either COPD or CHF alone. [27] The results of the present study were consistent with their study. There are some potential pathophysiological mechanisms that could explain the interaction between COPD and cardiovascular disease.…”
Section: Discussionsupporting
confidence: 93%
“…For instance, in a recent systematic review, reduction of left ventricular ejection fraction (LVEF) in patients with COPD was noted in 10–46% of patients depending on estimates [15]. Mortality rates are also higher in patients with concomitant HF and COPD [16].…”
Section: Introductionmentioning
confidence: 99%
“…A review of studies from different countries reports that 86 to 98% COPD patients have at least 1 other chronic disease with average number of comorbidities per individual ranging from 1.2 to 4.3 9 . Furthermore, the prevalence of comorbidities was found especially high in patients with severe COPD 10 . In addition, a recent meta-analysis highlights that Chronic obstructive pulmonary disease (COPD) represents a complex respiratory disorder characterized by persistent respiratory symptoms due to chronic airflow limitation caused by exposure to noxious particles/gases with an increased inflammatory response of the airways.…”
Section: Introductionmentioning
confidence: 98%
“…COPD is often accompanied by other concomitant chronic conditions that negatively impact prognosis and health status 6,7 . A large body of literature demonstrates that comorbidities are a widespread problem in COPD patients [8][9][10][11] . A review of studies from different countries reports that 86 to 98% COPD patients have at least 1 other chronic disease with average number of comorbidities per individual ranging from 1.2 to 4.3 9 .…”
Section: Introductionmentioning
confidence: 99%